2003
DOI: 10.1227/01.neu.0000043696.83722.8d
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Convection-enhanced Delivery into the Rat Brainstem

Abstract: Prolonged convection-enhanced delivery can be applied safely in the rat brainstem with no recognized limitations of V(d) and minimal histological changes beyond the site of infusion. Chronic brainstem infusions may enhance the potential application of convection-enhanced delivery for therapeutic purposes in treating diffuse pontine gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Local application of solutions in this manner is similar to convection-enhanced delivery. Numerous studies have shown that convection-enhanced delivery of molecules into the brain of rats, cats, primates, and humans did not result in any clinical deterioration, raised intracranial pressure, or histological evidence of disrupted cytoarchitecture other than at the site of cannula insertion (Occhiogrosso et al, 2003). What was often observed was pressure or dilution artifact due to local application of control solutions (saline or citrate) from cannula placed in proximity (50 -100 m) of the working electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Local application of solutions in this manner is similar to convection-enhanced delivery. Numerous studies have shown that convection-enhanced delivery of molecules into the brain of rats, cats, primates, and humans did not result in any clinical deterioration, raised intracranial pressure, or histological evidence of disrupted cytoarchitecture other than at the site of cannula insertion (Occhiogrosso et al, 2003). What was often observed was pressure or dilution artifact due to local application of control solutions (saline or citrate) from cannula placed in proximity (50 -100 m) of the working electrode.…”
Section: Methodsmentioning
confidence: 99%
“…A subsequent study by this group demonstrated that prolonged CED can safely achieve large volumes of distribution in the rat brainstem. 79 Slow infusion rates are generally used because high flow rates may increase intracranial pressure and may disrupt tissue architecture.…”
Section: New Therapeutic Perspective Strategiesmentioning
confidence: 99%
“…Firstly, convection-enhanced delivery is a method of local delivery that drives an infusate through the extracellular fluid in neural tissue using a continuous pressure gradient [61]. Experimental studies have shown that convection-enhanced delivery can achieve a local drug concentration 10,000-fold greater than that achieved by intravenous drug administration without causing significant systemic exposure [62, 63]. Secondly, local delivery of chemotherapeutic agents to the brainstem can be achieved via a cannulated screw attached to the skull of the animal [59].…”
Section: Future Directionsmentioning
confidence: 99%